5‐hydroxymethylfurfural conversion by fungal aryl‐alcohol oxidase and unspecific peroxygenase. (8th January 2015) - Carro, Juan; Ferreira, Patricia; Rodríguez, Leonor; Prieto, Alicia; Serrano, Ana; Balcells, Beatriz; Ardá, Ana; Jiménez‐Barbero, Jesús; Gutiérrez, Ana; Ullrich, René; Hofrichter, Martin; Martínez, Angel T.
<x xml:space="preserve">Abstract</x> Oxidative conversion of 5‐hydroxymethylfurfural (HMF) is of biotechnological interest for the production of renewable (lignocellulose‐based) platform chemicals, such as 2, 5‐furandicarboxylic acid (FDCA). To the best of our knowledge, the ability of fungal aryl‐alcohol oxidase (AAO) to oxidize HMF is reported here for the first time, resulting in almost complete conversion into 2, 5‐formylfurancarboxylic acid (FFCA) in a few hours. The reaction starts with alcohol oxidation, yielding 2, 5‐diformylfuran (DFF), which is rapidly converted into FFCA by carbonyl oxidation, most probably without leaving the enzyme active site. This agrees with the similar catalytic efficiencies of the enzyme with respect to oxidization of HMF and DFF, and its very low activity on 2, 5‐hydroxymethylfurancarboxylic acid (which was not detected by GC‐MS). However, AAO was found to be unable to directly oxidize the carbonyl group in FFCA, and only modest amounts of FDCA are formed from HMF (most probably by chemical oxidation of FFCA by the H2O2 previously generated by AAO). As aldehyde oxidation by AAO proceeds via the corresponding geminal diols (aldehyde hydrates), the various carbonyl oxidation rates may be related to the low degree of hydration of FFCA compared with DFF. The conversion of HMF was completed by introducing a fungal unspecific heme peroxygenase that uses the H2O2 generated by AAO to transform FFCA into FDCA, albeit more slowly than the previous AAO reactions. By adding this peroxygenase when FFCA production by AAO has been completed, transformation of HMF into FDCA may be achieved in a reaction cascade in which O2 is the only co‐substrate required, and water is the only by‐product formed.